Utilização de membranas no pós-tratamento de esgotos para reuso do permeado e aproveitamento do concentrado - Silva, Layane Priscila de Azevedo (2014)
The use of membrane filters in the post-treatment of sewage has been increasingly employed to obtain water quality, applicable to various forms of reuse. Despite the advantages presented using the permeate membranes, such as saving water and reducing water pollution, the concentrate generated in the process ends up being an inconvenience to the deployment of this technology due to lack of sustainable solutions for their management. Thus, the main objective of this research was to evaluate the use of membranes for microfiltration, ultrafiltration, nanofiltration and reverse osmosis concentrated in agriculture, using it as liquid fertilizer. The permeated membranes were also assessed in order to identify activities in which they could be reused. Five configurations were established from four types of membranes, so that each configuration represents a different system. The tests were conducted in batch mode, with triplicate for each configuration. The results indicated that permeated the microfiltration and ultrafiltration can be used in urban areas, in non-potable uses. Have the nanofiltration permeate can be reused in the industry, replacement cooling towers, and other non -potable uses required in the manufacturing unit. The permeate obtained in reverse osmosis met the intended uses for nanofiltration as well as the standards required for boiler feed, adding alkalizing being required to raise the pH to the recommended value. Concentrates generated in nanofiltration and reverse osmosis can be availed as liquid fertilizer in agriculture, but they must be diluted in the irrigation water, in order to adjust the salt concentration allowed for the least tolerant crops patterns